Overexpression of SlGRAS7 Affects Multiple Behaviors Leading to Confer Abiotic Stresses Tolerance and Impacts Gibberellin and Auxin Signaling in Tomato - Sidra Habib; Muhammad Waseem; Ning Li; Lu Yang; Zhengguo Li (International Journal of Genomics)
Abiotic stresses remain the key environmental issues that reduce plant development and therefore affect crop production. Transcription factors, such as the GRAS family, are involved in various functions of abiotic stresses and plant growth. The GRAS family of tomato (Solanum lycopersicum), SlGRAS7, is described in this study. We produced overexpressing SlGARS7 plants to learn more about the GRAS transcription factors. Plants overexpressing SlGARS7 (SlGRAS7-OE) showed multiple phenotypes related to many behaviors, including plant height, root and shoot length, and flowering time. We observed that many genes in the SlGRAS7-OE seedlings that are associated with auxin and gibberellin (GA) are downregulated and have altered sensitivity to GA3/IAA. SlGRAS7 was upregulated during abiotic stresses following treatment with sodium chloride (NaCl) and D-mannitol in the wild-type (WT) tomato. Tomato plants overexpressing SlGRAS7 showed more resistance to drought and salt stress comparison with WT. Our study of SlGRAS7 in tomato demonstrates how GRAS showed an integrative role, improving resistance to abiotic stresses and enhancing gibberellin/auxin signaling through reproductive as well as vegetative processes.